Preacher's strike - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. First mountain man (New York, N.Y.), 2025)
"Preacher is heading home to the mountains when he's approached by a wealthy European with an unusual proposition. He wants the legendary mountain man to track down his missing cousin--a reckless young woman who fled to America with her lover--and he's willing to pay a small fortune to find her. Preacher isn't one to get mixed up in the affairs of fancy foreigners, but he reluctantly agrees. The search is on. Striking westward from St. Louis, Preacher quickly begins to suspect that this search party is doomed. And this trail will lead to some very dead ends ... First off, they discover that the missing woman's American lover was killed by Teton Sioux years ago. Secondly, the murderous Knox gang heard about the rich European's fortune and plan to kidnap him for a ransom. Thirdly, a fierce band of Sioux warriors launch an attack on Preacher and his men. Things are looking pretty grim. But the biggest shock of all comes when Preacher finally meets the missing woman herself--and sees what she did to survive ..."--